2017
DOI: 10.5935/abc.20170014
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Radiofrequency Ablation of Renal Sympathetic Nerve on Anti-Hypertension in Canine

Abstract: BackgroundRadiofrequency ablation of renal sympathetic nerve (RDN) shows effective BP reduction in hypertensive patients while the specific mechanisms remain unclear.ObjectiveWe hypothesized that abnormal levels of norepinephrine (NE) and changes in NE-related enzymes and angiotensinconverting enzyme 2 (ACE2), angiotensin (Ang)-(1-7) and Mas receptor mediate the anti-hypertensive effects of RDN.MethodsMean values of systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Renal sympathetic overactivity and the renal plexus is an important component of the development of hypertension. 68 , 69 Sensory (afferent) renal nerves mainly sense the incoming information including volume changes and pressure changes, while and efferent renal nerves respond to the incoming information from afferent renal nerves, resulting in salt and water retention and activation of the RAAS, 68 , 70 , 71 , 72 which finally leads to an increase in systemic BP. Therefore, patients with hypertension characterized by sympathetic nervous system or RAAS overactivity are often considered sensitive to RDN.…”
Section: Discussionmentioning
confidence: 99%
“…Renal sympathetic overactivity and the renal plexus is an important component of the development of hypertension. 68 , 69 Sensory (afferent) renal nerves mainly sense the incoming information including volume changes and pressure changes, while and efferent renal nerves respond to the incoming information from afferent renal nerves, resulting in salt and water retention and activation of the RAAS, 68 , 70 , 71 , 72 which finally leads to an increase in systemic BP. Therefore, patients with hypertension characterized by sympathetic nervous system or RAAS overactivity are often considered sensitive to RDN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need of searching for alternative ways to effectively treat hypertension, particularly resistant hypertension ( Verloop, Voskuil & Doevendans, 2013 ; Azizi et al, 2015 ; deJong et al, 2016 ). Recent evidence indicated that hyperactivation of the renal sympathetic nerves could lead to decreased water and sodium reabsorption as well as renal blood flow and stimulate the renin-angiotensin-aldosterone system, leading to elevated BP ( Henegar et al, 2015 ; Fengler et al, 2017 ; Chen et al, 2017 ). During the past decade, a number of studies have extensively evaluated the regulation of BP by reducing renal sympathetic activity through invasive and noninvasive treatments ( Fengler et al, 2016 ; Mahfoud et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%